1991
DOI: 10.1063/1.350193
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of time-resolved electroluminescence and cathodoluminescence measurements on quantum well light emitters with varying barrier widths

Abstract: We present results of a comparative study of the time-dependent luminescence properties of multiple quantum well structures with varying barrier widths which are embedded in the active area of a light-emitting device. The carrier kinetics is investigated by different experimental approaches: Cathodoluminescence and electroluminescence experiments where excitation is on/off-modulated for the purpose of time-resolved measurements and time-resolved electroluminescence experiments in the small signal regime which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The EL signal at room temperature for forward currents in similar InGaAs/GaAs laser diodes can be easily detected for injection current densities that may be comparable with current densities in local junction sites of our CL--measured structures [4]. The similarity of EL and CL spectra in the case of GaAs laser diodes has been attributed to the case of a single QW [5]. The defects observed in the investigated structures were identified as oval defects.…”
Section: Resultsmentioning
confidence: 76%
“…The EL signal at room temperature for forward currents in similar InGaAs/GaAs laser diodes can be easily detected for injection current densities that may be comparable with current densities in local junction sites of our CL--measured structures [4]. The similarity of EL and CL spectra in the case of GaAs laser diodes has been attributed to the case of a single QW [5]. The defects observed in the investigated structures were identified as oval defects.…”
Section: Resultsmentioning
confidence: 76%
“…Understanding electron-hole separation caused by the internal electric field (E-field) is thus important and was analyzed by time-varying photo-luminescence spectra. 1) The intensity of the internal E-field was determined by measuring microwave radiation 2) in strained crystals that generated a piezoelectric E-field. Moreover, the effects of an internal E-field on carrier dynamics in polar crystals were measured in the sub-picosecond time scale, 3,4) which suggested that non-equilibrium carrier dynamics must be analyzed under the influence of an internal E-field.…”
mentioning
confidence: 99%